2021
DOI: 10.1186/s12915-021-01126-w
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modulation of Zebrafish exploratory statistics reveals constraints on individual behavioral variability

Abstract: Background Variability is a hallmark of animal behavior. It contributes to survival by endowing individuals and populations with the capacity to adapt to ever-changing environmental conditions. Intra-individual variability is thought to reflect both endogenous and exogenous modulations of the neural dynamics of the central nervous system. However, how variability is internally regulated and modulated by external cues remains elusive. Here, we address this question by analyzing the statistics of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 64 publications
1
19
1
Order By: Relevance
“…We thus sought to examine whether the thermal dependence of the ARTR endogenous dynamics could manifest itself in the animal navigational statistics. In order to do so, we used the results of a recent study ( Le Goc et al, 2021 ), in which 5 to 7 days old zebrafish larvae were video-monitored as they swam freely at constant and uniform temperature in the same thermal range (Figure 1E). We quantified the time scale of the turn direction persistence by assigning a discrete value to each turn bout: −1 for a right turn, +1 for a left turn (forward scouts were ignored).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus sought to examine whether the thermal dependence of the ARTR endogenous dynamics could manifest itself in the animal navigational statistics. In order to do so, we used the results of a recent study ( Le Goc et al, 2021 ), in which 5 to 7 days old zebrafish larvae were video-monitored as they swam freely at constant and uniform temperature in the same thermal range (Figure 1E). We quantified the time scale of the turn direction persistence by assigning a discrete value to each turn bout: −1 for a right turn, +1 for a left turn (forward scouts were ignored).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that spontaneous behavior in zebrafish larvae is not time-invariant but exhibits transitions between different regimes, lasting over minutes and associated with specific brain-states. These transitions can have no apparent cause ( Le Goc et al, 2021 ) or be induced by external (e.g. stimuli( Andalman et al, 2019 )) or internal cues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The exploratory behavior of zebrafish reveals overall symmetric distribution between the left and right turning angles ( Dunn et al., 2016 ; Goc et al., 2021 ). Since the general visual experience in real life should be directionally symmetric, we asked ourselves what the physiological necessity of the underlying set-point adaptation is.…”
Section: Discussionmentioning
confidence: 99%
“…In the same period, our cognitive capacity increased emphatically, spurring interest as to whether thermoregulation may influence neural development. Preliminary evidence for this hypothesis stems from recent zebrafish models, where the ambient water temperature was observed to drive persistent changes in exploratory behaviour [ 57 ]. These findings indicate that thermoregulatory mechanisms may drive intra-individual variability in vertebrate kinematics, likely by influencing neural circuits that regulate locomotor control [ 57 ].…”
Section: Postnatal Modifiers Of the Skin-brain Connectionmentioning
confidence: 99%
“…Preliminary evidence for this hypothesis stems from recent zebrafish models, where the ambient water temperature was observed to drive persistent changes in exploratory behaviour [ 57 ]. These findings indicate that thermoregulatory mechanisms may drive intra-individual variability in vertebrate kinematics, likely by influencing neural circuits that regulate locomotor control [ 57 ]. In humans, anecdotal evidence supporting a link between thermoregulation and neurodevelopment can be derived from parental reports of improved social interaction and language ability during febrile states in autistic children [ 58 ].…”
Section: Postnatal Modifiers Of the Skin-brain Connectionmentioning
confidence: 99%